ÇELİK KİRİŞ KOLONLARIN BURKULMA ANALİZİ - YAMAN, ZEYNEP DERE (Fırat Üniveristesi, 2000)
Bu çalışmada, eğilmeye ve eksenel basmç kuvveti etkisiyle burkulmaya çalışan Kiriş- Kolonların burkulma analizi yapılmıştır. Kiriş - Kolonların burkulma analizi için AISC, LRFD ve TS 648'de verilen gerçekleme formüllerinin teorik olarak nasıl çıkarıldığı ve şartnamelere nasıl yansıtıldığı araştırılmıştır. Ayrıca, Kiriş - Kolonların statik yükler altında elastik ve plastik dengesi de bu çalışmada incelenmiştir.

ın this study; the spraining analysis of beam - columns which are trying to bend down and sprain with the effect of axis pressure power are examined. For the spraining analysis of beam - columns, how the confirmation formulas are theoretically arised in AISC, LRFD and TS 648 and how they are reflected to the list of conditions are examined. And also, the elastic and plastic balance of beam - columns under static burdens are examined in this study.
The analysis of buckling of steel beam-columns
Keywords: İnşaat Mühendisliği; Civil Engineering